The long-term effect of explicit instruction on learners' knowledge on English articles. (March 2019) - Umeda, Mari; Snape, Neal; Yusa, Noriaki; Wiltshier, John
This study examines the role of explicit instruction in article semantics to L2 learners of English. Two types of generic sentences, expressed by different articles, were tested over time. An instruction group ( n = 21), a control group ( n = 16) and a native English speaker control group ( n = 9) participated in the study. The instruction group received nine 60-minute lessons across 9 weeks. A pre-test was administered to both groups before instruction began and four post-tests were given to both groups. The results from delayed post-tests show that the instruction group improved, but after one year little knowledge was retained. The findings suggest that explicit knowledge of articles is unlikely to be retained unless ongoing instruction is achieved.